Flouting Maxims in The Ellen DeGeneres Talk Show Episode Will Smith Full Interview with Ellen - Tia Bela Oktiva; Andang Saehu; Lili Awaludin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Abstract People can easily communicate well when people can apply maxim compliance principles in communicating. In reality, people do not always apply maxim compliance in communicating. When this happens during communication, it will cause a phenomenon called the floating maxim. This phenomenon occurs in The Ellen DeGeneres Talk Show which is the object of this research, with research questions: 1) What Maxims are flouted in The Ellen DeGeneres Talk Show Episode Will Smith Full Interview with Ellen? 2) What are the reasons of the characters flouting the Maxims in The Ellen DeGeneres Talk Show Episode Will Smith Full Interview with Ellen? The theory in this study uses the theory of Grice, Cutting and Leech. The objects in this research focus on Ellen and Smith. This study uses descriptive qualitative with content analysis. Technical analysis in this study uses the analysis of Vanderstoep and Johnston; Identifying, coding, discussing, and drawing conclusion. Based on the findings of the study, 33 data were found representing all types of flouting maxim and the reasons for flouting maxim. There are 3 data on the flouting maxim of quantity, 11 data on the flouting maxim of quality, 4 data on the flouting maxim of relevance, and 3 data on the flouting maxim of manner. While on the reasons of flouting maxim, there are 3 data on conflictive reason, 4 data on competitive reason, 2 data on convivial reason and 3 data on collaborative reason. Based on the results of the study, it was concluded that most of the characters in the show flouted the maxim of quality and competitive reasons for flouting maxim the maxim. Keywords: Pragmatics, Flouting Maxim, Reason for Flouting Maxim, Ellen DeGeneres Talk Show.